AGENTS ACTING ON CHOLINERGIC SYNAPSES - Mustanov T. B.; Djanaev G. Yu.; Mamadaliev Sh. I. (Web of Journals Publishing, 2024)
The autonomic nervous system (ANS) controls and regulates the whole system of bodily functions. It works silently, that is, acts unconsciously to maintain the rhythm of a large number of signal inputs and outputs and maintain a simple way of life. Most prominently, ANS is separated in two divisions—thoracolumbar outflow (sympathetic) and craniosacral outflow (parasympathetic)—which act on heart rate, digestion, respiratory rate, the sensory organs, major glands, urination, and sexual responses. By maintaining chemical–receptor (muscarinic and nicotinic receptors) interactions, this autonomic system generates smooth work output and maintains a balance between body and environment. Cholinergic agonists basically act on both muscarinic and nicotinic receptors and are clinically beneficial for urinary retentions, topically usable mitotic effects, and the promotion of saliva. To inhibit the hydrolysis of acetylcholine to cholinesterase, anti-acetylcholinesterase drugs, which show cholinergic effects, are used. Ganglia can be stimulated by anticholinesterase drugs through muscarinic receptors. Simultaneously, they can also cause bradycardia, hypotension, ganglionic stimulation, increase in heart rate, blood pressure, smooth muscles, glands, gastrointestinal movement, respiratory rate, urinary tracts, and eye. Chemical agents like atropine have the ability to block the muscarinic receptor, and certain synthetic chemical agents have significant properties to block (competitive antagonists) the nicotinic receptors. By blocking the muscarinic receptor, anticholinergic drugs cause tachycardia, block vasodepressor action, mydriasis and miotics, bronchodilation, relax the urinary bladder, urinary retention, decrease the sweat, saliva, tracheobronchial and lacrimal secretion, and increase the body temperature. This chapter provides a brief overview of cholinergic agonists, antagonists, and anticholinesterase drugs, their mechanisms, and their applications.
Keywords: M- and n-cholinomimetics, Acetylcholine, Carbacholin, Cyclodol, Anticholinesterase agents Physostigmine salicylate, Prozerin, Galantamine hydrobromide, Armin.